Firefly algorithm for facility layout problem optimization - Vargas-Pardo, Luisa Fernanda; Giraldo-Ramos, Frank Nixon (Visión Electrónica, 2021)
This paper shows the result of a research about the applications of bio-inspired algorithms in the field of production engineering in the Distrital University Francisco José de Caldas, covering the topics of industrial layout distribution in manufacturing plant layout. It is intended to seek the optimization of some problems of those fields, using artificial intelligence from the implementation of a firefly algorithm as metaheuristic planning tool and optimization of layout problem. With the goal of finding the best spatial allocation of work stations or cells. Theoretical concepts explored and results are presented. First, a state-of-the-art review on the subject was made, and then the possible solution algorithms were evaluated to identify the objective function to be optimized, to finally apply the firefly algorithm, and evaluate the results of performance against the Initial layout as the plant.